Parkin Maintains Robust Pacemaking in Human Induced Pluripotent Stem Cell‐Derived A9 Dopaminergic Neurons - Pu, Jiali; Lin, Lin; Jiang, Houbo; Hu, Zhixing; Li, Hong; Yan, Zhen; Zhang, Baorong; Feng, Jian (Movement disorders, 2023)
Background The degeneration of nigral (A9) dopaminergic (DA) neurons results in cardinal motor symptoms that define Parkinson's disease (PD). Loss‐of‐function mutations in parkin are linked to a rare form of early‐onset PD that is inherited recessively. Objective We generated isogenic human A9 DA neurons with or without parkin mutations to establish the causal relationship between parkin mutations and the dysfunction of human A9 DA neurons. Methods Using TALEN (transcription activator‐like effector nuclease)‐ or CRISPR/Cas9‐mediated gene targeting, we produced two isogenic pairs of naivetropic induced pluripotent stem cells (iPSCs) by repairing exon 3 deletions of parkin in iPSCs derived from a PD patient and by introducing the PD‐linked A82E mutation into iPSCs from a healthy subject. The four lines of isogenic iPSCs were differentiated to A9 DA neurons, which fired spontaneous pacemaking action potentials (AP) dependent on L‐type Ca2+ channels. Results The frequency of the pacemaking APs was significantly reduced by parkin mutations introduced to normal neurons. Consistent with this, isogenic repair of parkin mutations significantly increased the frequency from that observed in patient‐derived neurons. Conclusions The results show that parkin maintains robust pacemaking in human iPSC‐derived A9 DA neurons. The function is critical to normal DA transmission required for controlling voluntary locomotor activities. © 2023 International Parkinson and Movement Disorder Society. We repaired exon 3 deletions of parkin in induced pluripotent stem cells (iPSCs) from a Parkinson's disease (PD) patient and introduced the PD‐linked A82E mutation to normal iPSCs. Parkin mutations are sufficient and necessary to reduce the frequency of pacemaking APs in A9 dopaminergic neurons differentiated from these iPSCs.